Sustainability Assessment of Large Irrigation Dams in Senegal: A Cost-Benefit Analysis for the Senegal River Valley - Manikowski, Stanislaw; Strapasson, Alexandre (Frontiers in Environmental Science, 2016)
Starting in the 1970s, the Senegalese Government invested in the development of irrigated schemes in the Senegalese part of the Senegal River Valley (S-SRV). From that time to 2012, the irrigated schemes increased from 10,000 ha to more than 110,000 ha. In the meantime, the economic viability of these schemes started to be questioned. It also appeared that the environmental health and social costs might outweigh the benefits of irrigation. Using a life cycle assessment approach and project cost-benefits modelling, this study (i) quantified the costs and benefits of the S-SRV irrigated rice production, (ii) evaluated the costs and benefits of its externalities and (iii) discussed the irrigated rice support policy. The net financial revenues from the irrigated schemes were positive, but their economic equivalences. The economic return rate (EER) was below the expected 12% and the net present value (NPV) over 20 years of the project represented a loss of about US-19.6 million. However, if we also include the project’s negative externalities, such as the reduced productivity of the valley ecosystems, protection cost of human health, environmental degradation and social impacts, then the NPV would be much worse, approximately US-572.1 million. Therefore, the results show that to stop the economic loss and alleviate the human suffering, the S-SRV development policy should be revised using an integrated approach and the exploitation technology should aim at environmental sustainability. This paper may offer useful insights for reviewing the current Senegalese policies for the valley, as well as for assessing other similar cases or future projects worldwide, particularly in critical zones of developing countries.